Growth, education and the environment - Minna Selene Svane (Copenhagen Business School (CBS), 1999)
This dissertation consists of five self-contained chapters on fiscal policy within a two sector endogenously growing economy. The main focus of the dissertaion is on educational and environmental issues and in particular on the optimal subsidy to education and the optimal environmental policy. The frameworks, which are used to investigate these issues, are all extensions of the Uzawa-Lucas model of endogenous growth. Chapter 1 and 2 investigate the effects of factor income taxation and subsidization of educational effort, whereas Chapter 3, 4 and 5 investigate the transitional dynamics and the long run effects of environmental policy
hdl:10398/7927
Keywords: 650